Vpliv epiziotomije na pogostost poškodb perineja III. in IV. stopnje pri prvorodnicah v Sloveniji - Čeh, Anže (Obzornik zdravstvene nege, 2011)
Introduction: Episiotomy is perhaps one of the most frequently performed obstetric surgical procedures to facilitate delivery and prevent perineal lacerations and obstetric anal sphincter injuries. The article describes the effects of episiotomy on the incidence of severe third and fourth degree perineal lacerations. Methods: The author focused on the statistical data fromthe National Perinatal Information System of Slovenia for the period between 2005 and 2010. The data were analyzed by using basic statistics and presented with descriptive and quantitative methods. Results: Statistically significant correlation was identified between the frequency of episiotomies and perineal tears. Women who had undergone episiotomy suffered from the thirddegree perineal rupture/tear injury in 55.4 percent. Similar results wereconfirmed in women with the fourth degree perineal tears. Negative impactson the frequency of perineal damage can also be seen in stimulated and induced deliveries.Discussion and conclusions: The fact remains that episiotomy rates in Slovenia are too high. To reach the percentage of the Northern and Western Europe, it would be necessary to reduce the present episiotomy rates to below 25%. The research indicates that the extension of the second stage of the labor and the reduced labour stimulation with Oxytocinmight significantly diminish the incidence of severe perineal damages.
Keywords: childbirth; epiziotomija; perinej; porod; raztrganine